Checklist: Gender-inclusive actionable agro-advisories - Simelton, Elisabeth; Le Thi Tam (2020)
This checklist aims to assist producers and translators in developing agro-advisories (forecast and forecast-based advice) that are gender-inclusive and useful for both men and women farmers. It presents five indicators to determine the actionability of such agro-advisories: